Evaluation of the PhySens as a wrist-worn wearable in pitch detection and biomechanical workload estimation - Greenberg, E. M.; Thomas, S. J.; Kablan, J.; Condon, J.; Backstrom, E.; Lawrence, J. T. (Sports Health: A Multidisciplinary Approach, 2025)
Background: The volume and frequency of throwing activity are among the most significant risk factors for developing overuse injuries in youth athletes. Despite introducing systematic guidelines for `pitch counts,` throwing injuries continue to rise. Using technology to create enhanced measures of workload exposure in this unique population of athletes may help generate more effective and personalized injury prevention strategies.